2020
DOI: 10.18488/journal.68.2020.72.52.57
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Reference Evapotranspiration by Hargreaves and Blaney-Criddle Equations in Semi-Arid Climatic Conditions

Abstract: There are various equations for calculation of reference evapotranspiration (ETo), but the Penman-Monteith (PM FAO-56) equation has been considered as the standard ETo equation. The key problem of PM FAO-56 equation is that it uses large number of weather parameters like air temperature, wind velocity, humidity and sun radiation as input. These weather parameters are not accessible at all weather stations of the world especially in developing countries. So, ablatives ETo equations like Hargreaves (HG) and Blan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…They concluded that the Hargreaves-Samani equation calibrated with the maximum temperature is better than those calibrated with other meteorological data. Similarly, monthly ET values were computed using the modified Blaney-Criddle and Hargreaves-Samani equations, obtaining data from three stations located in the semi-arid climate regions of Pakistan and compared with PM-driven ET values [38]. Overall, it was stated in the study that both equations overestimated PMdriven ET values, although the findings of the Hargreaves-Samani method were superior to those of the modified Blaney-Criddle method.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…They concluded that the Hargreaves-Samani equation calibrated with the maximum temperature is better than those calibrated with other meteorological data. Similarly, monthly ET values were computed using the modified Blaney-Criddle and Hargreaves-Samani equations, obtaining data from three stations located in the semi-arid climate regions of Pakistan and compared with PM-driven ET values [38]. Overall, it was stated in the study that both equations overestimated PMdriven ET values, although the findings of the Hargreaves-Samani method were superior to those of the modified Blaney-Criddle method.…”
Section: Introductionmentioning
confidence: 91%
“…However, it is important to note that a zero correlation does not necessarily imply the absence of any relationship between the variables; it simply means that there is no linear relationship [67]. DET quantifies the model's goodness of fit and can be expressed as shown in Equation (38). It is a statistical metric that determines the proportion of the variance in the dependent variable that is explained by the independent variables in a regression model.…”
Section: Statistical Metricsmentioning
confidence: 99%
“…The accuracy of the HS and BC equations has been evaluated by several authors, comparing their results with the FAO-56 Penman–Monteith (PM) reference method; HS was the equation that attained the best fit in semi-arid regions [ 32 , 33 ]. Other authors state that the HS method works well in most climatic regions, except for wet areas where it tends to overestimate ET 0 [ 16 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%